The industrial uses of sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In Nigeria, for several years now, sorghum has taken the place of foreign cereals whose importation is strictly controlled. According to an ICRISAT publication Industrial use of sorghum, many small or medium-scale industries are now perfecting...